World Allergy Organization-McMaster University Guidelines for Allergic Disease Prevention (GLAD-P): Prebiotics. Issue 1 (December 2016) - Cuello-Garcia, Carlos; Fiocchi, Alessandro; Pawankar, Ruby; Yepes-Nuñez, Juan; Morgano, Gian; Zhang, Yuan; Ahn, Kangmo; Al-Hammadi, Suleiman; Agarwal, Arnav; Gandhi, Shreyas; Beyer, Kirsten; Burks, Wesley; et al.
Abstract Background The prevalence of allergic diseases in infants, whose parents and siblings do not have allergy, is approximately 10 % and reaches 20–30 % in those with an allergic first-degree relative. Intestinal microbiota may modulate immunologic and inflammatory systemic responses and, thus, influence development of sensitization and allergy. Prebiotics – non-digestible oligosaccharides that stimulate growth of probiotic bacteria – have been reported to modulate immune responses and their supplementation has been proposed as a preventive intervention. Objective The World Allergy Organization (WAO) convened a guideline panel to develop evidence-based recommendations about the use of prebiotics in the prevention of allergy. Methods The WAO guideline panel identified the most relevant clinical questions about the use of prebiotics for the prevention of allergy. We performed a systematic review of randomized controlled trials of prebiotics, and reviewed the evidence about patient values and preferences, and resource requirements (up to January 2015, with an update on July 29, 2015). We followed the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach to develop recommendations. Results Based on GRADE evidence to decision frameworks, the WAO guideline panel suggests using prebiotic supplementation in not-exclusively breastfed infants and not using prebiotic supplementation in exclusively breastfed infants. Both recommendations are conditional and based on very low certainty of the evidence. We found no experimental or observational study of prebiotic supplementation in pregnant women or in breastfeeding mothers. Thus, the WAO guideline panel chose not to provide a recommendation about prebiotic supplementation in pregnancy or during breastfeeding, at this time. Conclusions WAO recommendations about prebiotic supplementation for the prevention of allergy are intended to support parents, clinicians and other health care professionals in their decisions whether or not to use prebiotics for the purpose of preventing allergies in healthy, term infants.